Soluble CD38 significantly prolongs the lifespan of memory B-cell responses. - Liu, X; Hart, D; Macpherson, G; Good, M; Wykes, M (2008)
The development and maintenance of memory B cells (MBC) is dependent on germinal centres (GC) with follicular dendritic cell (FDC) networks. We have previously shown that FDC networks within GC of the spleen express a novel ligand for CD38 and that the administration of soluble CD38 induces an expansion of these cellular structures. We therefore used adoptive transfer studies to investigate whether the expansion of FDC networks with soluble CD38 affected the generation and maintenance of antigen-specific MBC. These studies found that the administration of soluble CD38 significantly extended the period after which MBC could be activated and that the frequencies of these cells also were increased. In conclusion, soluble CD38 appears to significantly extend the lifespan of antibody memory by increasing the numbers of MBC.